2007
DOI: 10.1111/j.1572-0241.2006.00946.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Gastric Emptying Is More Common than Gastroparesis in Patients With Autonomic Dysfunction

Abstract: Unexpectedly, more patients with autonomic dysfunction have rapid rather than delayed gastric emptying. The presence of diarrhea in patients with autonomic symptoms should prompt consideration for the presence of rapid gastric emptying. Conversely, the finding of rapid gastric emptying in patients with gastrointestinal symptoms should prompt consideration for the presence of underlying autonomic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 31 publications
1
44
2
1
Order By: Relevance
“…Rapid emptying has been recently observed as an accompanying factor in adult patients with cyclic vomiting syndrome (25,26). In one study, rapid GE was more common than delayed GE in symptomatic patients with autonomic dysfunction (27).…”
Section: Rapid Gementioning
confidence: 96%
“…Rapid emptying has been recently observed as an accompanying factor in adult patients with cyclic vomiting syndrome (25,26). In one study, rapid GE was more common than delayed GE in symptomatic patients with autonomic dysfunction (27).…”
Section: Rapid Gementioning
confidence: 96%
“…Interpreting why rapid gastric emptying is present in the vomiting-free period has led to speculation that there is an underlying autonomic dysfunction [7]. This is consistent with data that rapid gastric emptying is reported more commonly than delayed gastric emptying in symptomatic patients with autonomic dysfunction [16].…”
Section: Discussionmentioning
confidence: 74%
“…Mechanisms for GLS may include rapid movement of food to the small bowel resulting in small bowel distention and accompanied nausea, pain, and diarrhea, ie, similar symptoms to that of gastroparesis. 16,17 Other mechanisms may relate to proximal gastric activity, which might be better demonstrated by liquid gastric emptying, something not evaluated in this study. Indeed, patients with normal gastric emptying may be more similar to RGE than delayed gastroparesis as a mechanism for their symptomatology.…”
Section: Discussionmentioning
confidence: 90%
“…19 Our study supports prior studies reporting the poor correlation between clinical symptomatology and the diagnosis of gastroparesis. 17,18 This study did not look at response of tGES to pain, except as part of a larger symptoms spectrum. However, a recent report did examine pain, in relation to neuropathic changes in the GI tract, and found that some patients with abdominal pain do respond well to tGES.…”
Section: Discussionmentioning
confidence: 99%